2018
DOI: 10.3892/ijmm.2018.3602
|View full text |Cite
|
Sign up to set email alerts
|

Generation of haploid spermatids from chicken embryonal primordial germ cells

Abstract: In vitro production of functional spermatids has special significance in the research of spermatogenesis and the treatment of male infertility. Primordial germ cells (PGCs) are the precursors of oocyte and sperm, which generate the totipotent cells. Studies have shown that PGCs have the potential ability to develop meiotic spermatids in vitro. Here we have shown that retinoic acid (RA) leads to PGC differentiation, and SCF can improve the efficiency of induction. We indicate an efficient approach to produce ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Compared with gonad tissues at day 4.5, amphoteric PGCs represent lower heterogeneity, suggesting the uninitiated germ cell sex determination. A recent study has demonstrated that the amphoteric chicken PGCs could be induced by spermatogonial stem cells (SSCs) or oocytes via co-culture with sertoli cells or granulosa [42][43][44], which showed that PGC sex differentiation could be activated by somatic cells; this may explain different expression patterns of amphoteric gonad tissues with PGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with gonad tissues at day 4.5, amphoteric PGCs represent lower heterogeneity, suggesting the uninitiated germ cell sex determination. A recent study has demonstrated that the amphoteric chicken PGCs could be induced by spermatogonial stem cells (SSCs) or oocytes via co-culture with sertoli cells or granulosa [42][43][44], which showed that PGC sex differentiation could be activated by somatic cells; this may explain different expression patterns of amphoteric gonad tissues with PGCs.…”
Section: Discussionmentioning
confidence: 99%
“…In chicken PGCs, however, these in vitro goals can be relatively easily reached. For example, Ji et al. (2018) successfully generated haploid spermatids from chicken PGCs.…”
Section: New Epigenetic Research Possibilities Using Pgcsmentioning
confidence: 99%